The development of the 'Cancer Home-Life Intervention': An occupational therapy-based intervention programme for people with advanced cancer living at home. (3rd October 2021) - Lindahl-Jacobsen, Line Elisabeth; la Cour, Karen; Gregersen Oestergaard, Lisa; Sampedro Pilegaard, Marc; Peoples, Hanne; Brandt, Åse
Abstract: Background: Occupational therapy-based interventions may help people with advanced cancer to live actively despite their illness. However, there is limited evidence concerning what kinds of content intervention should encompass, and how this should be done. Objective: To describe the development and content of an occupational therapy-based intervention programme for people with advanced cancer living at home. Material and methods: In the development of the intervention, an evidence synthesis was performed based on a systematic literature search, data from a cross-sectional study, and experiences from an expert panel. Results: The programme contains six components: 1) An initial interview to select which of the other five components to address, based on the participants' individual needs. The interview addressed problems and needs of participants in relation to prioritized activities, in order to tailor the following components: 2) prioritisation of resources, energy and everyday activities; 3) adaptation of activities; 4) adaptation of posture and seating; 5) provision of assistive technology; and, 6) modification of the physical home environment. Conclusion: An occupational therapy-based intervention programme for people with advanced cancer living at home has been developed. The study generates knowledge and insights relevant to improving the treatment of this patient group.